2011
DOI: 10.1136/acupmed-2011-010006
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Application of Low-Frequency Electroacupuncture Improves High-Fructose Diet-Induced Insulin Resistance in Rats

Abstract: Background Insulin resistance is frequently present in obesity and during the development of type 2 diabetes mellitus. Objective The purpose of the present study was to investigate the effect of electroacupuncture (EA) on high-fructose diet (HFD)-induced insulin resistance. Methods Male Wistar rats were fed HFD for 4 weeks and developed insulin resistance. Insulin sensitivity was assessed by clamp. The number of animals was seven, eight and seven in the control, HFD and HFD+EA groups, respectively. AMPactivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…Peplow and Baxter [23] found that EAS of 15 Hz with 10 mA for 30 minutes and 60 minutes had a hypoglycemic effect in fasted type 2 diabetic rats. However, blood glucose was not altered following EAS with parameters of 15 Hz with 1–3 mA in type 2 diabetic rats and 20 Hz in type 1 diabetic rats [23, 24]. Similarly, although a different frequency EAS (10/100 Hz, 1–3 mA) was tried, blood glucose in STZ-induced diabetic rats was not significantly altered in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…Peplow and Baxter [23] found that EAS of 15 Hz with 10 mA for 30 minutes and 60 minutes had a hypoglycemic effect in fasted type 2 diabetic rats. However, blood glucose was not altered following EAS with parameters of 15 Hz with 1–3 mA in type 2 diabetic rats and 20 Hz in type 1 diabetic rats [23, 24]. Similarly, although a different frequency EAS (10/100 Hz, 1–3 mA) was tried, blood glucose in STZ-induced diabetic rats was not significantly altered in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies have studied the relationship between EA and AMPK. Tominaga et al [ 18 ] suggested that repeated EA therapy is capable of improving diet-induced insulin resistance, possibly via AMPK signaling activation in skeletal muscle. Immediately after EA stimulation, phospho-AMPKα (Thr172) was significantly higher in animals receiving EA than control animals.…”
Section: Introductionmentioning
confidence: 99%
“…All of the membranes were incubated at 4°C overnight with anti-Phos-AMPK α -Thr172 antibody (1 : 1000), or anti-AMPK α antibody (1 : 1000) or anti-GLUT4 (1 : 3000), or anti- α -tubulin antibody (1 : 1000) in 5% Carnation instant milk/TBS. After incubating with a secondary antibody (1 : 500) (Beijing Zhongshan Biotechnology, China) in 5% Carnation instant milk-TBS-Tween 20, the blots were developed using enhanced chemiluminescence according to the manual (Biological Industries, Beit Haemerk LTD, Israel) and exposed to X-ray film [22]. Normalization of protein expression was carried out using α -tubulin as control.…”
Section: Methodsmentioning
confidence: 99%